Complete Genome Sequences of 17 Clinical Campylobacter Jejuni Strains from Chile - Bravo-Zuniga, V (American Society for Microbiology, 2020)
Campylobacter jejuni is the leading cause of bacterial foodborne disease worldwide. Here, we report the complete annotated genomes and plasmid sequences of 17 Campylobacter jejuni strains isolated from patients with gastroenteritis in Santiago, Chile. © 2020 American Society for Microbiology. All rights reserved.